THE QUESTION CONCERNING THE APPLICATION OF THE CATEGORIES OF "SANITY" AND "DIMINISHED RESPONSIBILITY" IN MODERN FORENSIC PSYCHIATRY - Рзаєв Т. З. (World of Medicine and Biology, 2015)
This article discusses the concepts of sanity and diminished responsibility within psychiatry, psychology, criminology and other Sciences. Historical approach of the Russian and Western scientists to the concepts of sanity and diminished responsibility of persons who committed offences. Special attention is paid to people who have committed crimes in the sane state, and the issue of the identification of these persons have a mental illness after committing the crime, as well as being subject to compulsory measures of medical character. Legal criteria of public danger of the mentally ill is a committed act. Some scientists explain deviant behavior taking place in society social changes that disrupt his life. Because it destroys the harmony between people, some try to stick to the old norms and values (rituality, traditionalists), others focus on the newly emerging values and norms (avant-garde). If rules are not clear and contradictory, greater acceptance of individualism-Lit views on the role of compulsory medical measures in forensic psychiatric practice, as well as the problem of understanding mental anomalies of individuals who have committed crimes. The article raised the question of the role of prison psychiatry in assisting persons who have committed offences in a state of mental breakdown, and analyzed a comprehensive approach to different personality typologies, offenders and prosecuted. Thus, without denying the specific criminogenic role of mental disorders in the study of the causes of criminal behaviour of persons with mental disorder, in the sane and not exclude sanity conditions, it is necessary to consider not one but a combination of factors, including social factors and the personal characteristics of the individual. In our opinion, only multifactorial approach will allow us to develop the most effective measures of prevention of the wrongful conduct of such persons, and to shed light on the still controversial issue is the role of diminished responsibility in modern forensic psychiatry.
Keywords: forced measures of medical character imputed to the state; crimes committed by the mentally ill; mental assistance to convicts